2018
DOI: 10.1002/humu.23658
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent AFG3L2 and SPG7 mutations associated with syndromic parkinsonism and optic atrophy with aberrant OPA1 processing and mitochondrial network fragmentation

Abstract: Mitochondrial dynamics and quality control are crucial for neuronal survival and their perturbation is a major cause of neurodegeneration. m‐AAA complex is an ATP‐dependent metalloprotease located in the inner mitochondrial membrane and involved in protein quality control. Mutations in the m‐AAA subunits AFG3L2 and paraplegin are associated with autosomal dominant spinocerebellar ataxia (SCA28) and autosomal recessive hereditary spastic paraplegia (SPG7), respectively. We report a novel m‐AAA‐associated phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
(92 reference statements)
6
32
0
Order By: Relevance
“…25 The impaired balance of the different forms of OPA1 could be more severe in the presence of LOF variants leading to optic atrophy even in the absence of OPA1 mutations. 26 Furthermore, we confirm that the Ala510Val variant is the most common variant in patients (58.5%), showing a minor allele frequency of 0.5% in public databases, in agreement with other reports. 7,15,17,23,27 This variant was associated with a delayed onset of disease and a less complicated phenotype, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…25 The impaired balance of the different forms of OPA1 could be more severe in the presence of LOF variants leading to optic atrophy even in the absence of OPA1 mutations. 26 Furthermore, we confirm that the Ala510Val variant is the most common variant in patients (58.5%), showing a minor allele frequency of 0.5% in public databases, in agreement with other reports. 7,15,17,23,27 This variant was associated with a delayed onset of disease and a less complicated phenotype, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In this last patient, a family history of motorneuron disease (ALS) led the clinician to test for mutations in the SPG7 gene. Recently, both a single case of SPG7 presenting as a Parkinson's-like syndrome 11 and a patient with both AFG3L2 and SPG7 pathogenic variants and an early-onset optic atrophy with spastic ataxia and Ldopa-responsive parkinsonism have been reported 12 ; and in the Dutch study, a patient showed signs of parkinsonism, although this patient was under neuroleptics and the correlation was not as straightforward. 9 Therefore, the novel finding of parkinsonism as a frequent finding in the neurological examination of SPG7 patients, and the first report of a pure Pisa syndrome as initial presentation of underlying SPG7 disease, broadens the already wide spectrum of this disease.…”
Section: A Fifth Of Spg7 Patients Display Parkinsonismmentioning
confidence: 99%
“…1,4,9,10 The clinical spectrum of SPG7 disease continues to expand, and recently levodopa-responsive parkinsonism has been described in 2 patients. 11,12 Additionally, c.1529C>T (p.Ala510Val) variant in a heterozygous state has been found in 2 early-onset Parkinson's disease patients (EOPD). 13 SPG7 encodes paraplegin, a mitochondrial protein with a dual role as a metalloprotease responsible for assembling ribosomes and eliminating nonfunctional proteins in the mitochondria 14 and as a possible regulator of the mitochondrial permeability transition pore.…”
mentioning
confidence: 99%
“…The two best characterized stressors activating OMA1 are bioenergetic collapse and proteostatic stress following overload of quality control (QC) proteases (Head et al, 2009;Ehses et al, 2009). OMA1, for example, is activated following loss of AAA proteases YME1, AFG3L2, and SPG7, as well as scaffolding proteins, such as prohibitins and SLP-2, that organize YME1 and AFG3L2/SPG7, respectively, into microdomains in the inner membrane (Merkwirth et al, 2008;Ehses et al, 2009;Anand et al, 2014;Wai et al, 2016;Magri et al, 2018). Similarly, overload of QC proteases with aberrant mtDNA translation products in the setting of actininon treatment potently activates OMA1 prior to membrane potential collapse (Richter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The peptidase OMA1 is activated by mitochondrial stressors to cleave the active long form of OPA1 (L-OPA1) from its membrane anchor, leading to mitochondrial fragmentation and alterations in cristae structure (Head et al, 2009;Ehses et al, 2009). L-OPA1 processing by OMA1 also occurs upon loss of quality control proteases, such as YME1, AFG3L2, and SPG7, as well as inner membrane scaffolding proteins of the SPFH family, namely, prohibitins and SLP-2, that organize quality control proteases within inner membrane microdomains (Anand et al, 2014;Wai et al, 2016;Merkwirth et al, 2008;Ehses et al, 2009;Magri et al, 2018). Thus, OMA1 provides an escape mechanism for cristae with failed of protein quality control, separating dysfunctional mitochondrial units from the reticulum for degradation by autophagy (MacVicar and Lane, 2014).…”
Section: Introductionmentioning
confidence: 99%